On Being "Chinese Overseas": The Case of Chinese Indonesian Entrepreneurs - Juliette Koning (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2006)
Two things characterize the ethnic Chinese overseas: their subjection to discrimination and their over-representation (relative to the local people in the place of destination) in self-employment and entrepreneurship (Chan Kwok-bun 2004:xiii). Much has been written on ethnic Chinese firms in Southeast Asia. A major part of the scholarly attention has gone into trying to understand and explain business success. As such the debate has for a long time, in a rather dichotomizing way, been divided into capitalist (profit maximisation) and cultural (personal relationship) explanations as the main drivers for this so-called success. Since the late 1990s the debate has entered a new phase, sometimes referred to as the "revisionist mood‿ enhancing the deconstruction and de-mystification of ethic Chinese businesses. Interestingly enough the debate has been rather quiet on issues of identity and ethnic self-representation. This is where this paper tries to fill a gap. By focusing on the role and meaning of ethnicity and religion (as identity markers) in enterprise development, leadership and management styles, and decision-making and networking I hope to contribute to a better understanding of the significance of "being Chinese overseas‿ and "New-Born Christian‿ in entrepreneurial identity. Empirical case material on several new-born Christian ethnic Chinese entrepreneurs of small and medium sized companies in Indonesia shall be used to explore this delicate relationship. The overtly non-Christian socio-political domination and the contested citizenship position of ethnic Chinese in parts of the region shall be features of the necessary contextual discussion. Keywords: Ethnic Chinese, Indonesia, Entrepreneurship, New Order, Chineseness.
hdl:10398/7392
Keywords: 330